Modelos de pórtico plano para análise fisicamente não linear deestruturas de concreto armado - Leandro Mota Peres (2014)
The material nonlinear behavior of reinforced concrete structures, using one-dimensional models, has been studied according to two main approaches: the models that consider homogeneous cross sections and use stress-strain generalized relations, and models that decompose the section into smaller areas and use stress-strain laws. In this scenery, this work presents the formulation and computational implementation, into the system INSANE (INteractive Structural ANalysis Environment), of plane frame models for material nonlinear analysis using the Finite Element Method and stress-strain generalized relations. Numerical simulations of concrete structures allow to evaluate the model by comparing with experimental results and numerical results obtained with cross sections decomposed model implemented in the same system by Fonseca (2006).